2018
DOI: 10.1016/j.rmcr.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

A simple technique for thoracoscopic assisted placement of the distal limb of syringopleural shunts

Abstract: BackgroundSyringomyelia is an unusual accumulation of fluid within the spinal cord that may be associated with significant neurologic symptoms. Surgical drainage using various techniques is often required to reduce the intraparenchymal pressure and to alleviate symptoms. Syringopleural shunting seems to produce best results.Patients and methodsA simple technique to insert the distal limb of the syringopleural shunt into the pleural space is described in detail. The patient is placed in prone position. The syri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Two other studies were found in literature to date which utilised MIS approaches for the insertion of syringopleural shunts. A study by Bonatti and Kurtom [17] reported three cases (in two patients) of thoracoscopic assisted placement of the distal end of the catheter, which was generally well tolerated, with one patient showing immediate postoperative improvement, and the other showing cessation of disease progression after a redo procedure. Guest et al [18] reported seven cases of a percutaneous endoscopic approach for placement of the syringopleural or cystoperitoneal shunts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two other studies were found in literature to date which utilised MIS approaches for the insertion of syringopleural shunts. A study by Bonatti and Kurtom [17] reported three cases (in two patients) of thoracoscopic assisted placement of the distal end of the catheter, which was generally well tolerated, with one patient showing immediate postoperative improvement, and the other showing cessation of disease progression after a redo procedure. Guest et al [18] reported seven cases of a percutaneous endoscopic approach for placement of the syringopleural or cystoperitoneal shunts.…”
Section: Discussionmentioning
confidence: 98%
“…Several reports have described MIS technique for insertion of syringosubarachnoid shunts [14][15][16], however reports on syringopleural shunts are scarce. Here, we report our experience for MIS insertion of syringopleural shunts, and discuss other reported experiences of MIS syringopleural shunting in literature [17,18].…”
Section: Introductionmentioning
confidence: 85%